Slovenia: The Subsidy Policy Embedded in the Legal Environment of the EU – The Case of Slovenia - Bratina, Borut; Bohinc, Rado (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter explores the intricate relationship between state aid regulation and the sovereignty of the European Union (EU) Member States. The study is based on Art. 3 paras. (3) and (4) of the Treaty on the European Union (TEU), emphasising the EU’s commitment to establishing an internal market and economic union. While the internal market aims for a highly competitive social market economy, economic and social disparities among Member States necessitate establishing coordinated economic policies. Alongside the discussion on the system governing the protection of competition in the EU’s internal market, that is, EU competition law, the chapter also discusses state aid, considered a potential restraint on competition, and other actions like cartel agreements and abuse of dominance. The study argues that state aid, while generally undesirable in a market economy, may be a tool to prevent unwanted outcomes and achieve non-economic objectives. In examining EU competences, the study focuses on the exclusive competence of the EU in determining competition rules for the internal market, as outlined in Art. 3 of the Treaty on the Functioning of the European Union (TFEU). The unique supranational state aid control system significantly constrains Member States in economic, financial, environmental, and regional policy decisions. Notably, the chapter expands its scope to scrutinise Slovenian state aid law, especially in times of crisis. It explores the dynamics of state aid regulations during challenging economic periods (the COVID-19 pandemic and the war on Ukraine), shedding light on how Member States navigate the delicate balance between national interests and EU regulations. Using Slovenia as a case study, the chapter highlights the country’s constitutional amendments before joining the EU, underscoring how the delegation of the exercise of specific rights to the EU aligns with the principles of EU law. Keywords: state aid, sovereignty, EU competition law, internal market, Slovenian state aid law